2005
DOI: 10.1182/blood-2005-03-0984
|View full text |Cite
|
Sign up to set email alerts
|

A crucial role for T-bet in selectin ligand expression in T helper 1 (Th1) cells

Abstract: Proinflammatory T helper 1 (Th1) cells express high levels of carbohydrate ligands for the endothelial selectins, but the molecular basis for this phenotype is incompletely understood. We document here a significant role in selectin ligand formation for the recently described Th1 transcription factor T-bet. Th1 cells generated from T-bet ؊/؊ mice showed significantly lower levels of ligands for both E-selectin and P-selectin, compared with wild-type (WT) Th1 cells. Enforced expression of T-bet in WT Th0 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 32 publications
(77 reference statements)
3
43
2
Order By: Relevance
“…To analyze whether CD43 and CD44 also function as E-selectin ligands on NK cells, we pretreated DX5 ϩ CD90 Ϫ NK cells with a robust protease, bromelain, before lysate preparation. With the exception of ESL-1, an E-selectin ligand characteristically localized in the Golgi (34), bromelain digestion cleaves all cell surface E-selectin glycoprotein ligands on leukocytes (20,33,37). By flow cytometry, we first confirmed that bromelain treatment eliminated PSGL-1, CD43 and CD44 expression (data not shown).…”
Section: Glycolipid E-selectin Ligands Are a Major Component On Nk Cellsmentioning
confidence: 67%
See 1 more Smart Citation
“…To analyze whether CD43 and CD44 also function as E-selectin ligands on NK cells, we pretreated DX5 ϩ CD90 Ϫ NK cells with a robust protease, bromelain, before lysate preparation. With the exception of ESL-1, an E-selectin ligand characteristically localized in the Golgi (34), bromelain digestion cleaves all cell surface E-selectin glycoprotein ligands on leukocytes (20,33,37). By flow cytometry, we first confirmed that bromelain treatment eliminated PSGL-1, CD43 and CD44 expression (data not shown).…”
Section: Glycolipid E-selectin Ligands Are a Major Component On Nk Cellsmentioning
confidence: 67%
“…Leukocyte E-and P-selectin ligands engage in low-affinity, Ca 2ϩ -dependent binding interactions with E-and P-selectin constitutively expressed on dermal postcapillary venules and initiate their recruitment into inflamed skin (1,(3)(4)(5)(6)(7). Functional activity of these ligands is dependent on the expression on sialo-fucosylated carbohydrate moieties synthesized by ␣2,3 sialyltransferase IV (32,37,38) and FT4/7 (9, 10). Identification of authentic leukocyte E-and P-selectin ligands has been vigorously investigated, as the implication of their neutralization may provide a means for management of chronic inflammatory conditions, such as atopic/allergic dermatitis and psoriasis, and cutaneous lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…This finding prompted us earlier to suggest that T-bet would play an important role in FUT7 transcription and sialyl Lewis X expression in T lymphocytes (3). This proposal was supported by a recent study reporting a significant reduction of selectin ligand activity in T-bet deficient mice (25). The transfection of T-bet gene alone to cultured lymphoid cells, however, failed to confer appreciable selectin ligand expression either in a murine (26) or human system (see below), and the exact role played by T-bet in regulation of FUT7 transcription remains obscure.…”
Section: Resultsmentioning
confidence: 83%
“…The additional increased expression of fucosyl-and sialyltransferases in Th1 cells promotes synthesis of the selectin ligand sialyl-Lewis X (NeuAc␣2-3Gal␤1-4[Fuca1-3]GlcNAc), while Th2 helper cells lack sialyl-Lewis X sequences because a key fucosyltransferase, Fuc-T VII, is not expressed. Such differential glycosylation accounts for the selectin-mediated recruitment of CD4 Th1 cells to sites of inflammation (11)(12)(13)(14)(15)(16)(17).…”
Section: Activation Of Murine Cd4 ؉ and Cd8 ؉ T Lymphocytes Leads To mentioning
confidence: 99%